(untitled) (Світ фінансів, 2017)
Федоренко А. В. Додаткові джерела фінансування підприємств реального сектора й економічні механізми залучення інвестиційних ресурсів у виробництво. Розглянуто проблеми пошуку додаткових джерел фінансування підприємств реального сектора й активізації економічних механізмів залучення інвестиційних ресурсів у виробництво. З’ясовано причини, які гальмують інвестиційні процеси в Україні, та намічено шляхи щодо їх усунення. Запропоновано низку змін до податкового та корпоративного законодавства, спрямованих на активізацію інвестиційної діяльності та посилення стимулів до залучення фінансових ресурсів населення і юридичних осіб – інвесторів (резидентів та нерезидентів) у розвиток підприємств реального сектора. Федоренко А. В. Дополнительные источники финансирования предприятий реального сектора и экономические механизмы привлечения инвестиционных ресурсов в производство. Рассмотрены проблемы поиска дополнительных источников финансирования предприятий реального сектора и активизации экономических механизмов привлечения инвестиционных ресурсов в производство. Выяснены причины, тормозящие инвестиционные процессы в Украине, и намечены пути по их устранению. Предложен ряд изменений в налоговое и корпоративное законодательство, направленных на активизацию инвестиционной деятельности и усиление стимулов к привлечению финансовых ресурсов населения и юридических лиц – инвесторов (резидентов и нерезидентов) в развитие предприятий реального сектора. Fedorenko A. Additional sources of financing real sector enterprises and economic mechanisms for investment resources mobilization in production process. Introduction. Today traditional sources of investment resources for the finance of real sector are either virtually exhausted or unavailable to entities due to different objective or subjectivereasons. Therefore, solving the problem of economic growth inevitably faces finding and mobilization of additional funding of production process, which are currently unused as investments due to the lack of necessary legal or economic preconditions, mainly tax incentives. Purpose. In terms of the lack of resources to finance production process it is necessary to solve the dual objective: (i) to seek additional sources of alternative investments for real sector enterprises, (ii) to create the necessary conditions and intensify economic, especially tax incentives to attract financial investments in production process. Results. The problems of identifying additional sources of financing the real sector and enhancing economic mechanisms for attraction of investments into production process are considered. As additional sources of financing the development of enterprises the following are considered: 1) personal income and savings that are not currently used as an investment; 2) financial resources of entities that could be a source of investment, but today, for whatever reasons, are not available to enterprises. Barriers that slow down investment process in Ukraine are identified and relative means are suggested. Conclusion. The analysis allows to identify additional sources of funding for real sector enterprises that are not currently used as an investment, as well as to determine economic mechanisms for their mobilization. Changes to corporate and tax legislation are suggested in order to stimulate investment activity of population and legal entities – investors (residents and non-residents) on the stock market of Ukraine